2015
DOI: 10.1186/s12912-015-0073-y
|View full text |Cite
|
Sign up to set email alerts
|

I am only a nurse: a biographical narrative study of a nurse’s self-understanding and its implication for practice

Abstract: BackgroundThe personal is a vital part of professional nursing practice. From a psycho-social perspective, nurses produce and reproduce conceptions of the Self through experience. A literature search on nurses’ self-understanding in a psycho-social perspective yields no results. Hence, the aim of this study was to investigate personal and professional experiences that may have formed the self-understanding of a nurse, and how this self-understanding may have influenced her professional practice.MethodsUsing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
(51 reference statements)
0
26
0
1
Order By: Relevance
“…It is relational (Burnard, ; Campbell, ; Drew, ; Eckroth‐Bucher, , ; Jack & Miller, ; Jack & Smith, ; Kwaitek, McKenzie, & Loads, ; Rawlinson, ) because it allows oneself to analyse oneself in relation to other people and connect personal thoughts and feelings with that of others. It is extrapersonal (Burnard, ; Campbell, ; Drew, ; Eckroth‐Bucher, , ; Jack & Smith, ; Ramvi, ; Rowe, ; Vandemark, ) because it continuously expands beyond personal self and focuses on the analysis of the environment, where environment could be internal (i.e., mental, intellectual state, spirituality and so forth) and external (i.e., culture, relations, clinical settings). Self‐awareness as an extrapersonal process also means that expanding beyond personal self which enables individuals to identify sources of anxiety and gain control of those sources in future interactions with others (Jack & Smith, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is relational (Burnard, ; Campbell, ; Drew, ; Eckroth‐Bucher, , ; Jack & Miller, ; Jack & Smith, ; Kwaitek, McKenzie, & Loads, ; Rawlinson, ) because it allows oneself to analyse oneself in relation to other people and connect personal thoughts and feelings with that of others. It is extrapersonal (Burnard, ; Campbell, ; Drew, ; Eckroth‐Bucher, , ; Jack & Smith, ; Ramvi, ; Rowe, ; Vandemark, ) because it continuously expands beyond personal self and focuses on the analysis of the environment, where environment could be internal (i.e., mental, intellectual state, spirituality and so forth) and external (i.e., culture, relations, clinical settings). Self‐awareness as an extrapersonal process also means that expanding beyond personal self which enables individuals to identify sources of anxiety and gain control of those sources in future interactions with others (Jack & Smith, ).…”
Section: Resultsmentioning
confidence: 99%
“…() noted that acknowledging one's personal values could serve as an antecedent to engage in self‐awareness. Recognition of one's personal values could involve identifying one's historical, cultural and social understanding of oneself and one's family values (Eckroth‐Bucher, ; Ramvi, ), and identifying one's meaningful life patterns (Ramvi, ; Vandemark, ). Reflection and introspection, although noted as the strategies to develop self‐awareness, are also considered antecedents of self‐awareness (Gessler & Ferron, ; Severinsson, ; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Since Butler's seminal work in 1963 on life reviews (Butler, 1963), LSW has been found to serve a number of psychological functions. Activities related to LSW are valued for helping people to gain self-understanding (Ramvi, 2015) and recognise their self-worth (Chiang, Lu, Chu, Chang, & Chou, 2008). They help to reaffirm meaning in life by connecting people to life events and situations (Black & Hannum, 2015).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…A construção presente do profissional é, em parte, decorrente do sistema educacional, em que o ritmo, o modo e a caracterização decorrem em conformidade com a aquisição de conhecimentos inerentes à sua nova identidade profissional (Ramvi, 2015). Geralmente, os concluintes conseguem diferenciar das outras classes profissionais as atribuições dos enfermeiros (Oliveira, Lima e Baluta, 2016).…”
Section: Amadurecimento Profissional No Processo Formativounclassified